BK Virus Encephalitis in HIV-Infected Patients: Case Report and Review - Luciana Antoniolli; Rafael Borges; Luciano Z. Goldani (Case Reports in Medicine)
Encephalitis and meningitis due to BKPyV are unusual and emerging condition. Only a few cases of BKPyV encephalitis have been reported in hematopoietic stem cell transplant recipients, with the majority of cases presenting with concurrent hemorrhagic cystitis and HIV-infected patients. The authors report two HIV-infected patients with the diagnosis of BKPyV encephalitis and discuss the main clinical, diagnostic, and therapeutic aspects of this infection in patients with AIDS. Physicians should be aware to recognize the main clinical features and diagnose BKPyV central nervous infection in the setting of AIDS.